RESEARCH OF BLOOD TESTS FOR CHILDREN UNDER ONE YEAR - M. V. Penkina; M. N. Snegotskaya (Сеченовский вестник, 2013)
Many indicators of blood analysis vary considerably depending on the age of a child. Borderline values can be taken for pathology and a doctor can assign treatment, refer to a hematologist and delay vaccination of a child. To determine the possible changes in indicators of children's blood analysis the results of blood tests of certain groups of healthy children under one year were analyzed.